Pengaruh Lingkungan Sekolah Dan Disiplin Belajar Terhadap Hasil Belajar IPS Siswa Kelas IX UPTD SMP Negeri 4 Pematang Siantar T.A 2023/2024 - Maria Lumban Tobing; Benjamin Albert Simamora; Herlina Hotmadinar Sianipar (CV. KAMPUS AKADEMIK PUBLISING, 2023)
. The results showed that: 1) there is a positive and significant influence of the school environment on student learning outcomes, this result can be seen in the t test where the t value is greater than the t table (5.60> 1.660). 2) there is a positive and significant effect of learning discipline on student learning outcomes this result is seen in the t test where the t value is greater than the t table (5.76 > 1.660). 3) the school environment and learning discipline together affect student learning outcomes this result can be seen in the F test where the calculated F value is greater than the F table (112.64> 1.60955). The coefficient of determination test is known to be 0.2304, which means that 23.04% of environmental variables and learning discipline affect the social studies learning outcomes of class IX UPTD SMP Negeri 4 Pematang Siantar students.